Kerbau Toraja: Harga dan Keberlanjutan - Erwin Budiyanto David (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
Production costs become the main thing in determining the price but in certain commodities, it does not apply. In the commodity of art, objects’ production costs are not a price determination but the value that is on the object. The Toraja people have a unique view of the buffalo. They believe that buffalo is an animal that has value in Toraja customs, so the price of buffalo in Toraja is higher than other regions. This price determination is certainly seen based on the characteristics that exist in the Toraja buffalo. This study aims to determine buffalo pricing in terms of its cost elements and socio-cultural aspects. This research also intends to examine the ecological and social sustainability of this expensive price. The research method used is by direct interviews with the buffalo striped farmers resource. The result of this study indicates the cost element has a small role in determining the price of buffalo striped in Toraja. the high price of buffalo has a sustainable impact on ecological and social aspects because buffalo breeders will continue to work on the existence of buffalo striped so the Toraja traditional ceremony that requires buffalo striped can still be carried out for the people of Toraja.